PEMBERIAN FERMENTASI AMPAS SAGU (Metroxylon sago) DALAM RANSUM TERHADAP PERFORMA BROILER - Mihrani; Muhammad Zularsyil Salman; Hartina Beddu (Universitas Negeri Makassar, 2023)
This study aims to determine the Fermentation of Sago Dregs (Metroxylon Sago) in Feeds on Broiler Performance. This study was conducted in March – May 2022, in the poultry house of Campus 1 Polbangtan Gowa, Romang Lompoa Village, Bontomarannu District, Gowa Regency. The study method was compiled based on a completely randomized design (CRD) with a population of 48 broilers placed in 16 cage plots, each cage plot containing 3 chickens with 4 treatments each consisting of 4 replications. The treatment was given in broiler rations aged 1 – 29 days, each sample of the experimental design carried out in this study were P0 (without treatment), P1 (ration with 5% fermented sago dregs), P2 (ration with 10% fermented sago dregs), P3 (ration with 15% fermented sago dregs). Parameters observed were ration consumption, weight gain, and feed conversion. Data were analyzed using ANOVA test and continued with Duncan's test. The results of the study showed that in P1 the provision of rations with 5% fermentation of sago dregs, does not give a significant difference in the percentage of feed conversion, but P1 gave a significant difference in the feed consumption test of 1870.62 and body weight growth of 1159.70, so it can be recommended that the best treatment is P1 (giving 5% fermented sago dregs).